2018
DOI: 10.1159/000495591
|View full text |Cite
|
Sign up to set email alerts
|

Beta Adrenergic Receptors Stimulation Attenuates Phosphorylation of NF-κB and IκBα in Hyperglycemic Endothelial Cells

Abstract: Background/Aims: NF-κB induces transcription of a number of genes, associated with inflammation and apoptosis. In this study, we have investigated the effect of β-adrenergic receptor stimulation on NF-κB and IκBα in HUVECs. Methods: Human umbilical vein endothelial cells (HUVECs) were cultured in high and low glucose concentrations. All HUVECs were treated with different concentrations of isoproterenol and propranolol for different time periods. The analytical procedures consisted of Western Blot, ELISA, DCFH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…39 Safia and colleagues showed that, in vitro, beta-adrenergic receptor stimulation reduced EC apoptosis and decreased the level of reactive oxygen species generation via the NF-jB/IjBa pathway. 40 Their study demonstrated that hyperglycemia could be an apoptotic stimulus to trigger NF-jB release and activation. 40…”
Section: Similar Pathways Of the Ace2 Receptor And Other Endothelial Receptors Responsible For Induction Of Ec Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Safia and colleagues showed that, in vitro, beta-adrenergic receptor stimulation reduced EC apoptosis and decreased the level of reactive oxygen species generation via the NF-jB/IjBa pathway. 40 Their study demonstrated that hyperglycemia could be an apoptotic stimulus to trigger NF-jB release and activation. 40…”
Section: Similar Pathways Of the Ace2 Receptor And Other Endothelial Receptors Responsible For Induction Of Ec Dysfunctionmentioning
confidence: 99%
“…40 Their study demonstrated that hyperglycemia could be an apoptotic stimulus to trigger NF-jB release and activation. 40…”
Section: Similar Pathways Of the Ace2 Receptor And Other Endothelial Receptors Responsible For Induction Of Ec Dysfunctionmentioning
confidence: 99%
“…The IKK complex can be activated by lipopolysaccharides (LPSs), viral proteins, oxygen free radicals, cytokines and other stimuli; it then phosphorylates the Ser36 and Ser32 residues in the SRD region of the N-terminus of IκBα (Traenckner et al, 1995;Hayden and Ghosh, 2004;Kato et al, 2012;Ko et al, 2017;Liu et al, 2018;Safi et al, 2018), leading to ubiquitination and the subsequent degradation of the IκBα in proteasome (Figure 2). IKK-dependent IκBα phosphorylation at the serine residues occurring in the cytosol is a key step in the release of active NF-κB and its nuclear translocation (Yazdi et al, 2017).…”
Section: Ikk-dependent Phosphorylationmentioning
confidence: 99%
“…β2ADR has been reported to enhance the anti-inflammatory properties in some organs and tissues, like immune [ 11 ], urinary [ 12 ], nervous [ 13 ], cardiovascular [ 14 ], and respiratory systems [ 10 ]. This receptor affects its mentioned functions mainly through activating the canonical signaling pathway β2ADR/ Gs protein (Gs protein, Gs)/cAMP/protein kinase A (Protein kinase A, PKA) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the agonists and blockers of beta-2 adrenergic receptors have been shown to create the anti-inflammatory functions in the different tissues. On one hand, as the anti-inflammatory agents, usage of some beta-2 adrenergic agonists (Beta-2 Adrenergic Agonist, BAA) have been recommended to treat the immune, urinary, nervous, cardiovascular, and respiratory dysfunctions [ 10 – 14 ]. Beta blockers (Beta Blocker, BB), on the other hand, decrease the inflammatory signs in the diseases like rheumatoid arthritis, respiratory disorders, and cancers [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%